2021
DOI: 10.29303/jppipa.v7ispecialissue.828
|View full text |Cite
|
Sign up to set email alerts
|

Gender Analysis in terms of Attitudes and Self-Efficacy of Science Subjects for Junior High School Students

Abstract: The purpose of this study was to determine the comparison of students' attitudes and self-efficacy based on gender, and to determine the relationship between students' attitudes and self-efficacy towards science subjects. This research uses quantitative research with survey method. The sample in this study was 74 students from SMPN 1 Muaro Jambi in Muaro Jambi district. The sampling technique used is purposive sampling. There are two instruments in this study, namely attitudes towards science and self-efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
6
1
2
Order By: Relevance
“…2-tailed > 0.05, which is 0.876. The results of this study differ from studies which state that there are differences in students' self-efficacy in Science learning in the female and male groups (Ernawati et al, 2021a;Retni et al, 2021;Aurah, 2017). In addition, the results of research by Ernawati et al (2021b), show that the male group has higher self-efficacy in Science learning than the female group.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…2-tailed > 0.05, which is 0.876. The results of this study differ from studies which state that there are differences in students' self-efficacy in Science learning in the female and male groups (Ernawati et al, 2021a;Retni et al, 2021;Aurah, 2017). In addition, the results of research by Ernawati et al (2021b), show that the male group has higher self-efficacy in Science learning than the female group.…”
Section: Resultscontrasting
confidence: 99%
“…Several factors that affect students' self-efficacy both are external and internal factor, one of them is gender (Ernawati et al, 2021a). Gender is very familiar with one's identity, both for men and women which refer to masculinity and femininity (Ernawati et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Base on descriptive statistical test results were obtained a description of student responses to learning videos in gymnastics material in PJOK subjects found that class XI with a percentage of 37.1% in the good category was superior to class X with a percentage of 34.3% in the good category. Based on Table 8, the description of the student's discipline character in the learning video with gymnastic material in the PJOK subject on the indicator Getting used to being present on time it was found that class XI a percentage of 35.4% in the good category was superior to class X with a percentage of 33.3% in the good category (Amin, Alimni, et al, 2021;Ernawati et al, 2021;Kamid, Sabil, et al, 2021). Based on Table 9, the description of the student's discipline character in the learning video with gymnastic material in the PJOK subject on the indicator Getting used to obeying the rules, it was found that class X with a percentage of 57.1% in the good category was superior to class XI with a percentage of 51.4% in the good category.…”
Section: Discussionmentioning
confidence: 99%
“…The waiting tubang custom is a custom regarding inheritance which is prioritized to the eldest daughter (Arifin, 2020;Darmaji, Astalini, et al, 2019;Velinda et al, 2018). But on the other hand, waiting for tubang is also interpreted as someone who is in charge of waiting for a large family gathering place with the agreement that this task is given to the eldest daughter (Ernawati, Asrial, Kurniawan, Nawahdani, et al, 2021;Septiana et al, 2016;Wulandari et al, 2021). The custom of waiting for tubang causes boys to have to apply the character of hard work in themselves (Kamid, Syaiful, et al, 2021;Maison et al, 2021;Rasyidin & Fitriani, 2021).…”
Section: Introductionmentioning
confidence: 99%